Robotics Education in Schools: Ac n Inclusive and Scalable Pedagogical Approach - Itacaramby, Gabriela; Cabral, João L.; Pastrana, M. A.; Sanchez, William Humberto Cúellar; Baptista, Roberto de Souza; M., Daniel (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper presents a pedagogical proposal for introducing robotics education to children aged 8 to 17 in public schools, with a specific focus on 3D printing and robot construction. Grounded in constructionist learning theory, the approach combines theoretical instruction, hands-on workshops, and formative assessments to foster meaningful engagement in STEM. The methodology was implemented in a series of biweekly workshops conducted by the Titans robotics team in partnership with a local school in Brasilia, Brazil. Instructional content was delivered using open-source tools and adapted to low-resource settings to promote accessibility and inclusion. Evaluation through pre- and post-tests demonstrated significant learning gains, particularly in concepts initially unfamiliar to students. The results support the effectiveness of structured, practical robotics education in fostering STEM competencies at an early age. Limitations and directions for future expansion, including broader implementation and longitudinal tracking, are discussed.